PERANCANGAN PERANGKAT LUNAK BASE STATION ROBOT SEPAK BOLA BERODA DENGAN QT CREATOR - Nathanael, Indra; Mudjirahardjo, Panca; Muttaqin, Adharul (Jurnal Mahasiswa TEUB, 2024)
This research aims to design base station software used in the Indonesian Wheeled Soccer Robot Contest (KRSBI-B) competition. The base station plays a role in the KRSBI-B communication scheme, which is to receive commands from the referee box and send them to the client. In this study, the base station is designed using Qt Creator as an IDE on the Ubuntu Operating System (OS). In general, the base station is divided into 3 main points, namely communication with the referee box, communication with the robot/client, and an interface to interact with the user. Communication between the base station and the referee box is designed using the TCP/IP protocol. Communication between the base station and the client is designed using the UDP protocol. The basestation interface is designed using the Qt Framework as the backend and Qwidget as the output. In this study, testing was also carried out consisting of functionality testing and performance testing. Functionality testing is done to test whether the base station can work, while performance testing is done to test the performance of the base station during use. Based on the test results, the designed base station has successfully received data from the referee box and sent and received data to the clientcorrectly. The designed base station is ready to use and meets the requirements for the KRSBI-B competition. Keywords— Base Station, Qt Creator, TCP/IP, UDP.